Assessing the Effect of Hormonal Contraceptives on Oxidative Stress and Lipid Metabolism in Reproductive Age Women: Hormonal Contraceptives and Oxidative Stress - Mahmood, Anjum; Khan, Rakhshinda Inam; Humayun, Anjum; Salman, Farzana; Afridi, Sanodia; Anwar, Saadia (Pakistan Journal of Health Sciences, 2025)
Women of reproductive age frequently use hormonal contraceptives for family planning and regulating menstrual cycles. There is growing apprehension, however, regarding the potential long-term metabolic and cardiovascular effects of these contraceptives due to their impact on oxidative stress and lipid metabolism. Objective: To assess the impact of hormonal contraceptive use on oxidative stress markers and lipid profile parameters in reproductive-age women. Methods: This comparative cross-sectional study encompassed 150 women aged 18 to 40 years, evenly split into users and non-users of hormonal contraceptives. From each participant, blood samples were drawn to assess oxidative stress Markers Malondialdehyde (MDA), Total Antioxidant Capacity (TAC), Superoxide Dismutase (SOD), catalase, Glutathione Peroxidase (GPx), as well as lipid profile parameters such as total cholesterol, triglycerides, LDL-C, HDL-C, and the LDL/HDL ratio. For the analysis, appropriate parametric and non-parametric tests were applied for the statistical comparisons. Results: Hormonal contraceptive users had significantly higher MDA levels and reduced TAC, SOD, GPx, and catalase activity, indicating elevated oxidative stress and impaired antioxidant defenses (p < 0.001). Lipid profile analysis revealed significantly increased total cholesterol, triglycerides, and LDL-C, along with reduced HDL-C and elevated LDL/HDL ratios among users compared to non-users (p < 0.001). Conclusions: Hormonal contraceptive use in reproductive-age women is associated with increased oxidative stress and an unfavorable lipid profile. These biochemical alterations may raise the risk of cardiovascular complications with long-term use. Regular monitoring and preventive strategies, including lifestyle counseling and antioxidant support, may help mitigate these risks.